Patient-Specific Retinal Organoids Recapitulate Disease Features of Late-Onset Retinitis Pigmentosa - Gao, Mei-Ling; Lei, Xin-Lan; Han, Fang; He, Kai-Wen; Jin, Si-Qian; Zhang, You-You; Jin, Zi-Bing (Frontiers in Cell and Developmental Biology, 2020)
Although an increasing number of disease genes have been identified, the exact cellular mechanisms of retinitis pigmentosa (RP) remain largely unclear. Retinal organoids (ROs) derived from the induced pluripotent stem cells (iPSCs) of patients provide a potential but unvalidated platform for deciphering disease mechanisms and an advantageous tool for preclinical testing of new treatments. Notably, early-onset RP has been extensively recapitulated by patient-iPSC-derived ROs. However, it remains a challenge to model late-onset disease in a dish due to its chronicity, complexity and instability. Here, we generated ROs from late-onset RP proband-derived iPSCs harboring a PDE6B mutation. Transcriptome analysis revealed a remarkably distinct gene expression profile in the patient ROs at differentiation day (D) 230. Changes in the expression genes regulating cGMP hydrolysis prompted the elevation of cGMP levels, which was verified by a cGMP enzyme-linked immunosorbent assay (ELISA) in patient ROs. Furthermore, significantly higher cGMP levels in patient ROs than in control ROs at D193 and D230 might lead to impaired formation of synaptic connections and the connecting cilium in photoreceptor cells. In this study, we established the first late-onset RP model with a consistent phenotype using an in vitro cell culture system and provided new insights into the PDE6B-related mechanism of RP.